Sanitation and Waste Management Education: Stunting Prevention for Posyandu Cadres and Toddler Mothers in Liliba Village - Telan, Albina Bare; Agustina, Agustina; Dukabain, Olga; Yulia, Yulia (Pascasarjana Universitas Mataram, 2025)
Stunting is still a public health problem in Indonesia, including in Liliba Village, Kupang City, which has a high stunting incidence rate. One of the main factors contributing to stunting is poor environmental sanitation and suboptimal waste management. This community service activity aims to improve the knowledge and skills of Posyandu cadres and mothers under five in implementing good environmental sanitation and managing waste with the Takakura method. The methods used include education, training, simulation, and evaluation through pre-test and post-test. The results of the activity showed an increase in participants' understanding, which was reflected in the increase in post-test scores compared to pre-test. In addition, participants were able to apply organic waste management skills to compost, which supports family food security and creates a healthier environment. With continuous assistance, it is hoped that behavior change in maintaining environmental cleanliness can contribute to efforts to prevent stunting in the community.